The Prevalence of Back Pain and the Pattern of Complaints in Pregnant Women at the Gatak Community Health Centers - Mutiara, Farrah Rizky; Fatmarizka, Tiara (Academic Physiotherapy Conference Proceeding, 2022)
Background: Musculoskeletal complaints experienced by pregnant women have an impact on comfort in carrying out daily activities, one of which is back pain. Back pain experienced by pregnant women usually starts in the second and third trimesters due to various factors, one of which is a change in posture. Based on the location of the complaint, back pain is divided into 3, namely:low back pain (LBP), pelvic girdle pain (PGP), and lumbo pelvic pain (LPP). In 2019 in Indonesia there were 70% cases of back pain experienced by pregnant women, this needs to be known so that it can be used as a precaution for pregnant women and be preventive in their pregnancy. Objective: to determine the prevalence of the location pattern and the degree of back pain felt by pregnant women. Methods: This type of research is an observational study with a cross-sectional approach. The sampling technique in this study used incidental techniques with 194 samples with questionnaires. Results: Based on the results of the study, the highest prevalence of back pain was found in pregnant women at the Gatak Health Center, namely pain with a low back pain location pattern of 61.3% (121 respondents) with a moderate degree of pain with an average pain result of 4.6. Conclusion: Pregnancy back pain is normal because of changes in posture and other risk factors and the most frequent pattern of pain location is Low Back Pain with moderate pain degree (60.3%), followed by Lumbo Pelvic Pain location pattern 21.1% and Pelvic Girdle Pain 17.5%. 3% (121 respondents) with moderate pain degree with an average pain result of 4.6.